# Solve for m 4/5*(m-1)-1/5m=1 45⋅(m-1)-15m=1
Simplify 45⋅(m-1)-15m.
Simplify each term.
Apply the distributive property.
45m+45⋅-1-15m=1
Combine 45 and m.
4m5+45⋅-1-15m=1
Multiply 45⋅-1.
Combine 45 and -1.
4m5+4⋅-15-15m=1
Multiply 4 by -1.
4m5+-45-15m=1
4m5+-45-15m=1
Move the negative in front of the fraction.
4m5-45-15m=1
Combine m and 15.
4m5-45-m5=1
4m5-45-m5=1
Simplify terms.
Combine fractions with similar denominators.
4m-4-m5=1
Subtract m from 4m.
3m-45=1
3m-45=1
3m-45=1
Multiply both sides of the equation by 5.
3m-4=1⋅(5)
Remove parentheses.
3m-4=1⋅(5)
Multiply 5 by 1.
3m-4=5
Move all terms not containing m to the right side of the equation.
Add 4 to both sides of the equation.
3m=5+4
Add 5 and 4.
3m=9
3m=9
Divide each term by 3 and simplify.
Divide each term in 3m=9 by 3.
3m3=93
Cancel the common factor of 3.
Cancel the common factor.
3m3=93
Divide m by 1.
m=93
m=93
Divide 9 by 3.
m=3
m=3
Solve for m 4/5*(m-1)-1/5m=1

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top